Analisis Akuntabilitas Pengelolaan Dana Punia di Pura Tirta Bhuana Sari, Gorontalo - Kadek Ria Sudiantari; Ronald S. Badu (Al-Buhuts, 2023)
This study aims to find out: the process of managing punia funds at Thirta Bhuana Sarri Temple and also the form of accountability for managing punia funds, in this study researchers were directly involved in the research process. The research method used is a qualitative method with the theory of tri hita karana and also with the teachings of tattwam asi. Data obtained through interviews, observation, and documentation. The results of the study show that the process of managing punia funds is carried out according to the agreement of the people at Thirta Bhuana Sari Temple and also the four elements of accountability that are implemented, namely: accountability, transparency, responsiveness and control. The four elements of accountability have been carried out in a simple way for a long time. The element of accountability in the management of the punia fund concerns all people because the punia fund is a religious contribution given by the people in taluditi so that it can create a sense of mutual trust between the administrators and also the people at the Thirta Bhuana Sari Temple